Effect of recombinant ADAMTS‐13 on microthrombosis and brain injury after experimental subarachnoid hemorrhage - Vergouwen, M. D. I.; Knaup, V. L.; Roelofs, J. J. T. H.; Boer, O. J.; Meijers, J. C. M. (Journal of thrombosis and haemostasis, 2014)
Summary Background A common complication after aneurysmal subarachnoid hemorrhage (SAH) is delayed cerebral ischemia (DCI), which is associated with vasospasm and other mechanisms such as microthrombosis. ADAMTS‐13 activity plays a role in the prevention of thrombus formation in the cerebral microvasculature. Previously, we observed that patients with DCI have lower levels of ADAMTS‐13. Objectives To examine whether recombinant human ADAMTS‐13 (rADAMTS‐13) reduces cerebral microthrombus formation and brain injury in an experimental mouse model of SAH including wild‐type and ADAMTS‐13−/− mice. Methods Experimental SAH was induced with the prechiasmatic blood injection model. The following experimental groups were investigated: (i) C57BL/6J mice (n = 10); (ii) C57BL/6J mice (n = 10) treated with rADAMTS‐13 20 min after SAH; (iii) ADAMTS‐13−/− mice (n = 10); and (iv) ADAMTS‐13−/− mice (n = 10) treated with rADAMTS‐13 20 min after SAH. Mice were killed at 48 h. Results are presented as means with standard errors of the mean. Results Infusion with rADAMTS‐13 reduced the extent of microthrombosis by ~ 50% in both wild‐type mice (mean fibrinogen area: 0.28% ± 0.09% vs. 0.15% ± 0.04%; P = 0.20) and ADAMTS‐13−/− mice (mean fibrinogen area: 0.32% ± 0.05% vs. 0.16% ± 0.03%; P = 0.016). In addition, rADAMTS‐13 reduced brain injury by > 60% in both wild‐type mice (mean microglia area: 0.65% ± 0.18% vs. 0.18% ± 0.04%; P = 0.013) and ADAMTS‐13−/− mice (mean microglia area: 1.24% ± 0.36% vs. 0.42% ± 0.13%; P = 0.077). Conclusions Our results support the further study of rADAMTS‐13 as a treatment option for the prevention of microthrombosis and brain injury after SAH.